Low glucose availability potentiates the effects of metformin on model T cell activation and exhaustion markers in vitro - Repas, Jernej; Peternel, Lea; Sourij, Harald; Pavlin, Mojca (Frontiers in Endocrinology, 2023)
Modulation of immune cell metabolism is one of promising strategies to improve cancer immunotherapies. Metformin is an anti-diabetic drug with potential anti-cancer effects, ranging from normalization of blood glucose and insulin levels, direct anti-proliferative effects on cancer cells to emerging immunomodulatory effects on anti-tumor immunity. Metformin can reduce tumor hypoxia and PD-L1 expression, as well as normalize or improve of T cell function and potentiate the effect of immune checkpoint inhibitors, making it a promising adjuvant to immunotherapy of tumors with poor response such as triple negative breast cancer (TNBC). However, although the effects of metformin on cancer cells are glucose-dependent, the role of glucose in modulating its effect on T cells has not been systematically studied. We thus investigated the effect of metformin as a function of glucose level on Jurkat cell and PBMC T cell models in vitro. While low metformin concentrations had little effect on T cell function, high concentration reduced proliferation and IFN-γ secretion in both models and induced a shift in T cell populations from memory to effector subsets. The PD-1/CD69 ratio was improved by high metformin only in T cells from PBMCs. Low glucose and metformin synergistically reduced PD-1 and CD69 expression and IFN-γ secretion in T cells from PBMCs. Low glucose level itself suppressed Jurkat cell function due to their limited metabolic plasticity, but had limited effects on T cells from PBMCs apart from reduced proliferation. Conversely, high glucose did not strongly affect either T cell model. Metformin in combination with glycolysis inhibitor 2-deoxy-D-glucose reduced PD-1 in Jurkat cells, but also strongly suppressed their function. However, low, physiologically achievable 2DG concentration itself reduced PD-1 while mostly maintaining IL-2 secretion and, interestingly, even strongly increased IFN-γ secretion regardless of glucose level. Overall, glucose metabolism can importantly influence some of the 2 This is a provisional file, not the final typeset article effects of metformin on T cell functionality in tumor microenvironment. Additionally, we show that 2DG could potentially improve the anti-tumor T cell response.